Bevacizumab combined with re-irradiation in recurrent glioblastoma - She, Lei; Su, Lin; Liu, Chao (Frontiers in Oncology, 2022)
Background Glioblastoma is characterized by rich vasculature and abnormal vascular structure and function. Currently, there is no standard treatment for recurrent glioblastoma (rGBM). Bevacizumab (BEV) has established role of inhibiting neovascularization, alleviating hypoxia in the tumor area and activating the immune microenvironment. BEV may exert synergistic effects with re-irradiation (re-RT) to improve the tumor microenvironment for rGBM. Purpose The purpose of this study was to evaluate the safety, tolerability, and efficacy of a combination of BEV and re-RT for rGBM treatment. Methods In this retrospective study, a total of 26 rGBM patients with surgical pathologically confirmed glioblastoma and at least one event of recurrence were enrolled. All patients were treated with re-RT in combination with BEV. BEV was administered until progression or serious adverse events. Results Median follow-up was 21.9 months for all patients, whereas median progression-free survival (PFS) was 8.0 months (95% confidence interval [CI]: 6.5–9.5 months). In addition, the 6-month and 1-year PFS rates were 65.4% and 28.2%, respectively. The median overall survival (OS), 6-month OS rate, and 1-year OS rate were 13.6 months (95% CI: 10.2–17.0 months), 92.3%, and 67.5%, respectively. The patient showed good tolerance during the treatment with no grade > 3 grade side event and radiation necrosis occurrence rate of 0%. Combined treatment of gross total resection (GTR) before re-RT and concurrent temozolomide during re-RT was an independent prognostic factor that affected both OS and PFS in the whole cohort (OS: 0.067, 95% CI: 0.009–0.521, p = 0.010; PFS: 0.238, 95% CI: 0.076–0.744, p = 0.038). Conclusion In this study, re-RT combined with concurrent and maintenance BEV treatment was safe, tolerable, and effective in rGBM patients. Moreover, GTR before re-RT and selective concurrent temozolomide could further improve patient PFS and OS.